From harvest to health: Challenges for developing biofortified staple foods and determining their impact on micronutrient status - Hotz, Christine; McClafferty, Bonnie (SAGE Publications, 2007)
Background. The use of conventional breeding techniques and biotechnology to improve the micronutrient quality of staple crops is a new strategy to address micronutrient deficiencies in developing countries. This strategy, referred to as “biofortification,” is being developed and implemented through the international alliance of HarvestPlus to improve iron, zinc, and vitamin A status in low-income populations. Objective. The objective of this paper is to review the challenges faced by nutritionists to determine and demonstrate the ability of biofortified crops to have an impact on the nutritional and health status of target populations. Methods. We reviewed available published and unpublished information that is needed to design and evaluate this strategy, including issues related to micronutrient retention in staple foods, micronutrient bioavailability from plant foods, and evidence for the efficacy of high-micronutrient-content staple foods to improve micronutrient status. Results. Further information is needed on the retention of micronutrients in staple foods, in particular of provitamin A carotenoids, when stored and prepared under different conditions. The low bioavailability of iron from staple foods and the ability to demonstrate an impact on zinc status are specific challenges that need to be addressed. In target countries, infections and other micronutrient deficiencies may confound the ability to affect micronutrient status, and this must be taken into account in community-based studies. Conclusions. Information to date suggests that biofortification has the potential to contribute to increased micronutrient intakes and improved micronutrient status. The success of this strategy will require the collaboration between health and agriculture sectors.